Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Acylation of anisole with long-chain carboxylic acids over wide pore zeolites - Wagholikar, S. G.; Niphadkar, P. S.; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2007)
The acylation of anisole with long-chain carboxylic acids (hexanoic, octanoic and decanoic) has been studied over three large pore zeolites-beta (BEA), faujasite (FAU) and mordenite (MOR). The acylation of anisole with the long chain acids produced mainly the ketone (4-methoxy phenyl alkyl ketone) and small amounts of the ester (phenyl alkanoate). The results revealed the reaction to be influenced by the type of zeolite and its Si/Al ratio (acidity) besides the chain length (carbon number) of the carboxylic acid. In the acylation of anisole with hexanoic acid, the activity of the zeolites increased with dealumination as it led to the generation of mesopores that resulted in a decrease in diffusion resistance of the zeolites. The reactivity of the acids in the acylation reaction was found to decrease with increase in the carbon number. The experimental data have been fitted into a pseudo first order kinetic model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Anisole; decanoic acid; hexanoic acid; octanoic acid; zeolites

Alkylation of anisole with 1-hexene and 1-hexanol over zeolite H-beta - Surse, P. V.; Wagholikar, S.; Mayadevi, S.; Sivasanker, S. (Reaction Kinetics Mechanisms and Catalysis, 2011)
An examination of the kinetics of the alkylation of anisole with 1-hexene and 1-hexanol to produce alkylates over zeolite H-beta is presented. Anisole alkylation is found to occur by a set of parallel reactions when hexene is used as the alkylating agent. When hexyl alcohol is the alkylating agent, the reaction follows a multi-step parallel-series mechanism to form monoalkylates and dihexylether. With 1-hexene, a group of isomeric alkylates, viz., ortho-2-hexyl anisole (2-OHA), ortho-3-hexyl anisole (3-OHA), para-2-hexyl anisole (2-PHA), and para-3-hexyl anisole (3-PHA) was obtained. With hexanol, the olefin (hexene) and dihexyl ether were obtained additionally. The influence of process parameters like temperature, catalyst quantity, and alkylating agent on reaction behavior is reported.
Keywords: Alkylation; Anisole; H-beta; Hexene; Hexyl alcohol